Active BiVO4 Swimmers Propelled by Depletion Gradients Caused by Photodeposition. Issue 15 (22nd January 2023) - Wittmann, Martin; Voigtmann, Maximilian; Simmchen, Juliane
Abstract: Artificial active matter often self‐propels by creating gradients of one or more species or quantities. For chemical swimmers, most frequently either O2 or H + that are created in certain catalytic reactions are causing the interfacial flows which drive the self‐propulsion. While the palette of reactions is extending constantly, especially toward more bio‐compatible fuels, the depletion of species is often overlooked. Here, the photodeposition of metal species on BiVO4 micro swimmers is considered. During the photodeposition reaction, metal ions are removed from the solution creating a depleted region around the particle. The ability of this depletion to drive active motion of artificial micro swimmers, as well as the influences of different metal ions and counter ions on the motion are investigated and cross compared. Abstract : Chemical active matter mostly self‐propels by a gradient, created through the production of some species. The photodeposition of different noble metals on the surface of BiVO4 swimmers depletes the particle surrounding fluid of metal ions to achieve vivid propulsion and is therefore one of the first depletion reactions causing motility, including orientation changes in the particles.